Persepsi tentang Kepemimpinan Perempuan; Scientific and Religious Reviews - Mukhlisah AM (Program Studi Manajemen Pendidikan Islam UIN Sunan Ampel Surabaya, 2014)
Purposes: This article will describe new conclude conception to explain women and leadership. It may be called as integrative point that based on scientific and religious authority perception. Theoretical Framework: Scientific perception mean was how academic community campaign the growth of women or female leadership. A Religious authority perception meant is Indonesian Moslem organization, such as: Nahdlatul Ulama’, Muhammadiyah, and Majelis Ulama’ Indonesia. Research Method; Kinds of methodology which used is a library research. There are two different sources of data; books and news record. Socio-Anthropological and phenomenology’s approaches also will used as tool to explain tendencies of science and religious authority perception. Result; Based on science women leadership is just and fairness to access all of human rights. Even if, there are psychological differences between men and women, it urged to lie on balance of life. In addition, there are supporting perception which built by religious authority. Some of them, actually in Indonesia, do support the gender equality in public field. Implication: This article is just a foundation to understand how academic-community in University makes their perception, and also, how religious individual and society create their consensuses, about Women or Female Leadership